Sustainable development: Paradoxes, misunderstandings and learning organizations (2012)
Purpose: Sustainability is, in itself, the idea of a harmonic answer to the dual nature of the most pressing problem for global society. Most of the problems dealing with sustainability concern its dual and contradictory nature. That paradoxical reality is in no way a unique feature of sustainability; its universal pervasiveness is demonstrated by the attention that Western and Eastern philosophies have given to it. This paper seeks to describe paradoxes that arise in managerial and organizational learning processes and proposes a taxonomy. It pays special attention to the central paradox of 'complexifying' and to reductionism-holism in science. Design/methodology/approach: The work is based on the theories of organizational learning and managerial cybernetics, under the paradox view of management. Findings: The study shows the relevance of the paradox view to management understanding of the complexity of sustainability, its controversial nature; and how the latter relates to epistemology and to the complementarity of analytical and synthetics methods in research and science. It also demonstrates that, at organizational levels, harnessing tensions that emerge from natural paradoxical situations enhances sustainable oriented decision-making. Research limitations/implications: The paper builds a bridge toward scientific communities that, working on sustainability and/or complexity, are unaware of the important contribution of cybernetics, especially Ashby's work and the VSM's relevance to the examination of complex societal issues. Practical implications: The paper provides a platform to enquire on the implications of societal learning on sustainability, and on de facto global digital networks emerging from over ideologized constituents that, in the name of the greenness of the environment and of a just society, fail to see how rapidly global society is positively changing after the dark years of the Cold War. Originality/value: The paper reviews current developments on the paradox view of management, and proposes a taxonomy of paradoxes based on managerial cybernetics and organizational learning. © Emerald Group Publishing Limited.